1993
DOI: 10.1182/blood.v82.9.2714.bloodjournal8292714
|View full text |Cite
|
Sign up to set email alerts
|

Acute thrombocytopenic purpura in relation to the use of drugs

Abstract: The relation of acute thrombocytopenic purpura (TP) to the use of drugs was investigated in a case-control study conducted in eastern Massachusetts, Rhode Island, and the Philadelphia region; 62 cases over the age of 16 years with acute onset and with a rapid recovery were compared with 2,625 hospital controls. After control for confounding by multiple logistic regression, use of the following drugs in the week before the onset of symptoms was significantly associated: trimethoprim/sulfamethoxazole (relative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Our estimate is consistent with that provided by a case-control study, which provides an attributable risk of quinine-quinidine induced thrombocytopenia of 26 cases of every 1 million users. 13 Notably, the relative risk of quinine associated thrombocytopenias in our analysis using diltiazem as a comparator is significant. Incidence rate ratios comparing quinine with diltiazem were 4.2 overall for ITP and 3.4 for the first 30 days of exposure.…”
Section: Discussionmentioning
confidence: 75%
“…Our estimate is consistent with that provided by a case-control study, which provides an attributable risk of quinine-quinidine induced thrombocytopenia of 26 cases of every 1 million users. 13 Notably, the relative risk of quinine associated thrombocytopenias in our analysis using diltiazem as a comparator is significant. Incidence rate ratios comparing quinine with diltiazem were 4.2 overall for ITP and 3.4 for the first 30 days of exposure.…”
Section: Discussionmentioning
confidence: 75%
“…Because only few reports were identified and because interpretation of the reports was often difficult, a concise summary of each patient report is presented in Tables 3-7. Articles reporting thrombocytopenia associated with quinine-containing beverages were identified but not included in the Tables because quinine is well recognized as one of the most common causes of drug-induced isolated thrombocytopenia (8,9). In addition to the 27 articles included in the Tables, six articles were identified that described seven patients with thrombocytopenia associated with quinine-containing beverages (16)(17)(18)(19)(20)(21).…”
Section: Resultsmentioning
confidence: 99%
“…The ISI Web of Knowledge interface was used to search the [1] Current Contents Connect and [2] Web of Science databases; the OvidSP interface was used to search the [3] Allied and Complementary Medicine (AMED), [4] Cochrane Database of Systematic Reviews, [5] EMBASE, [6] International Pharmaceutical Abstracts, and [7] MEDLINE databases. Reports were also sought from the [8] Natural Medicines Comprehensive Database, [9] FDA MedWatch Database, [10] International Bibliographic Information on Dietary Supplements Database (IBIDS), and [11] the Health and Wellness Resource Center. The websites for these databases are provided in the legend of Table 1.…”
Section: Data Sources and Searchesmentioning
confidence: 99%
See 2 more Smart Citations